2021
DOI: 10.1037/xge0000852
|View full text |Cite
|
Sign up to set email alerts
|

Reasoning strategies explain individual differences in social reasoning.

Abstract: The dual-strategy model of reasoning suggests that when people reason they can either use (a) a statistical strategy which generates an estimation of conclusion likelihood using a rapid form of associative processing or (b) a counterexample strategy which identifies potential counterexamples to a conclusion using a more conscious working memory intensive process. Previous results suggest that strategy use is a strong individual difference that represents a broad distinction in the way that information is proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…These results add to the growing body of evidence that individual differences in strategy use are an important determinant of information processing in a variety of different contexts (e.g., Gagnon-St-Pierre et al, 2020;Markovits et al, 2018, b). These results also add some weight to existing analyses of the effects of simple repetition on people's beliefs in claims for which they have no real prior knowledge.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…These results add to the growing body of evidence that individual differences in strategy use are an important determinant of information processing in a variety of different contexts (e.g., Gagnon-St-Pierre et al, 2020;Markovits et al, 2018, b). These results also add some weight to existing analyses of the effects of simple repetition on people's beliefs in claims for which they have no real prior knowledge.…”
Section: Discussionsupporting
confidence: 62%
“…This leads them to process similar information in different ways. For example, a recent study has shown that when given a text that supports the existence of gender differences, Statistical reasoners show higher degrees of sexist attitudes, while Counterexample reasoners do not (Gagnon-St-Pierre et al, 2020). Thus, one explanation of the present results would be that Statistical reasoners simply consider the single disconfirmation as another source of information that is weighted equally to that of the repeated claims, while Counterexample reasoners construct a more focused model of this information for which disconfirmation has a much stronger weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, these results add to a growing base of empirical results that are consistent with the idea that strategy use is an important individual difference. The fact that such differences have been observed not only with standard deductive reasoning tasks but also with belief-biased reasoning (de Chantal et al, 2019;Markovits et al, 2017), judgements involving processing of negative emotions (Markovits, Trémolière, & Blanchette, 2018b), mental rotation tasks (Markovits, 2019), and social biases (Gagnon-St-Pierre et al, 2020) and now with very fast reasoning, suggests that strategy use is a determinant of differences in the more general processing of information, one that goes well beyond standard deductive reasoning tasks.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a recent study has found that under time pressure, reasoning strategy is a much stronger predictor of performance than cognitive capacity (Markovits et al, 2021). In addition, reasoning strategy has been shown to predict performance on a variety of very different forms of judgments, including gender differences in negative emotion processing (Markovits, Trémolière, & Blanchette, 2018) and spatial rotation (Markovits, 2019), general differences in susceptibility to a variety of biases (Gagnon-St-Pierre et al, 2020), and the extent to which disconfirmation reduces belief in fake news (Gratton & Markovits, 2021).…”
mentioning
confidence: 99%